The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0100-204x2006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de QTL associados à simbiose entre Bradyrhizobium japonicum, B. elkanii e soja

Abstract: Resumo -O objetivo deste trabalho foi identificar QTL (locos de caráter quantitativo), utilizando marcadores do tipo microssatélites (SSR), relacionados à fixação biológica de nitrogênio (FBN), em uma população F 2:7 de cultivares de soja (Glycine max) com diferentes capacidades de FBN, Bossier (alta) e Embrapa 20 (média). Foram mapeados 16 marcadores, distribuídos em seis grupos de ligação, cobrindo uma região de 5% do genoma (151,6 cM). A análise de regressão identificou 12 associações significativas em quat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
2
22
1
5
Order By: Relevance
“…On the other hand, Wiebold et al (1981) observed a low to moderate (36% to 56%) heritability in the broad sense, for net photosynthesis of individual leaves, in the initial F 3 and F 4 generations using an infrared gas analysis system at temperatures varying from 29 to 31 o C. Table 1 shows heritability values for W ST , n N e W N of 87.47%, 18.70% e 32.02%, respectively. These values are in agreement with the observations of Santos et al (2006) who estimated heritability values of 49% for stem dry mass, 30% for nodule number, and 33% for nodule dry mass, in a segregating population composed of 157 recombinant inbred lines derived from the cross between two soybean cultivars identified as contrasting for biological nitrogen fixation capacity. Therefore, it can be concluded that the evaluated traits are under environment effects, as well as that the present population can be used in studies aimed at evaluating heritability of such traits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, Wiebold et al (1981) observed a low to moderate (36% to 56%) heritability in the broad sense, for net photosynthesis of individual leaves, in the initial F 3 and F 4 generations using an infrared gas analysis system at temperatures varying from 29 to 31 o C. Table 1 shows heritability values for W ST , n N e W N of 87.47%, 18.70% e 32.02%, respectively. These values are in agreement with the observations of Santos et al (2006) who estimated heritability values of 49% for stem dry mass, 30% for nodule number, and 33% for nodule dry mass, in a segregating population composed of 157 recombinant inbred lines derived from the cross between two soybean cultivars identified as contrasting for biological nitrogen fixation capacity. Therefore, it can be concluded that the evaluated traits are under environment effects, as well as that the present population can be used in studies aimed at evaluating heritability of such traits.…”
Section: Discussionsupporting
confidence: 91%
“…Mansur et al (1993) that the LGs C1, C2 and D1 have loci associated with the traits leaf area and maturity of the soybean. The identification of a QTL associated with W ST in the LG L confirms the observation that in this LG there is a QTL associated with WST (Santos et al, 2006) and plant height of G. max (Lee et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…While the rj 1 allele [15] conditions a restriction of nodulation with a broad range of rhizobia, other genes like Rj 2 [15], Rj 3 [16], Rj 4 [17] , Rj 5 and Rj 6 [18] restrict nodulation only with defined members of bradyrhizobia serogroups. Furthermore, Nicolás et al [19,20], Santos et al [21] found that nodulation of soybean cultivars is also under the control of QTL (quantitative traits) such that soybean cultivars can be grouped in high and low nodulating ones.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (2006) relacionaram o efeito do QTL à herdabilidade da característica. Assim, a identificação de QTL de pequeno efeito requer grande quantidade de marcadores estrategicamente ordenados.…”
Section: Resultsunclassified